The impact of Hmong women's gender role endorsement on decision-making - Yang, Kao Lee (My University, 2011)
Previous research has shown that Hmong women are taking on more modern gender role views as opposed to keeping their traditional, patriarchal views of gender roles. This research investigates Hmong women?s endorsement of modern and traditional gender roles and how it affects their decision in a decision-making scenario with a Hmong man. There were a total of 32 Hmong women participants. Each participant completed a Hypergender Ideology Scale, which measured their adherence to traditional gender roles, followed by instructions to read a scenario involving a man and a woman making decisions. Each decision that was made in the scenarios represented the gender role view (modern vs. traditional) of the woman. An average Hypergender score revealed that participants held modern gender role views. However, correlations of the Hypergender score were significant with some chores from the traditional scenario but not the modern scenario. These results suggest that participants held modern gender role beliefs but still endorsed traditional gender roles. Hmong women grow up in a culture that holds traditional gender role beliefs and where men are the main family decision-makers. As a result, Hmong women rarely find themselves in positions where they can make a decision that will impact their family. They may have felt conflicted to answer according to their modern gender role views.
Keywords: Sex role--United States--Social life and customs; Hmong American women; Hmong (Asian people); Hmong American women--Ethnic identity; Hmong American women--Cultural assimilation